BS EN ISO 1346. Fibre ropes. Polypropylene split film, monofilament and multifilament (PP2) and polypropylene high-tenacity multifilament (PP3). 3-, 4-, 8- and 12-strand ropes. (23rd June 2020) - British Standards Institution,
No abstract available